Effective VCR operations using efficient tree mechanism and scheduling for video streams in peer to peer networks. (1st January 2014) - Rayan, Arockia Xavier Annie; Palanichamy, Yogesh
Video-on-Demand (VOD), a popular streaming application is omnipresent. An active solution to solve the problem of VCR operations in VOD is laid out. There is the need to provide media streams with at most no delay which is achieved by combining the static full stream scheduling (SFSS) with the data management using earliest reachable merge tree (ERMT). This is done in a peer to peer multicast environment where the clients register to a media stream server (MSS) for requests. The new-movie request and the interactive playback are handled for scheduling at the request schedule server (RSS) which is between the peer to peer clients and the MSS. There is a great deal in subduing the force of delay in much larger scale with this set up. The simulation result endorses the validity of the inclusion of a separate schedule server.